Організація освіти дорослих у Франції та Бельгії - Орос Ільдіко; Oros Ildiko; Orosz Ildikó (Харківський національний університет імені В. Н. Каразіна, 2019)
Резюме. Що стосується роботи з дорослим населенням Франції, то нами виділено особливості нової форми організації неперервної професійної освіти дорослих у цій країні – освітньої структури ГРЕТА. Національна освітня структура ГРЕТА в наш час є основною організацією, що займається неперервною професійною освітою дорослих у Франції. До складу Бельгії входять 3 мовні спільноти – фламаномовна, франкомовна та німецькомовна. На тлі федерального устрою, мовного розшарування населення існують проблеми. У країні ведеться боротьба з неграмотністю дорослого населення, в результаті чого підвищується загальний рівень освіти.

Abstract. The purpose of the article is to uncover the organization of adult education in France and Belgium. As for working with the adult population of France, we have highlighted the peculiarities of a new form of organization of continuing vocational education of adults in this country – the educational structure of GRETA. The reason for the emergence in France of such a structure as GRETA was the consequence of general trends in the development of adult education. GRETA's national educational structure in our time is the main organization involved in the continuing vocational education of adults in France. Adult education in France differs significantly from the education of adults in other European countries, because in its organization, the funding plays a significant role in the state, the Ministry of National Education of France and regional education authorities. The leading methodological approach in the process of adult education is the cultural approach, which defines the direction of other approaches - systemic, axiological and activity, that is, traditional as well as non-traditional (hermeneutic, procedural-design) approaches. Adult vocational education is an integral part of the French education system. As a socio-pedagogical phenomenon, adult education is regarded as a factor in socialization and a means to attain a certain level of education, general culture and professional competence, which corresponds to the social and personal needs of adults as subjects of education and work. Belgium consists of 3 language communities – flamanoval, francophone and german-speaking. Against the backdrop of the federal system, the linguistic stratification of the population has problems. The country is fighting the illiteracy of the adult population, resulting in increased literacy of the population. Migration processes are one of the factors leading to the emergence of functional illiteracy in Belgium. The training of functional literacy of adults in Belgium is based on the principles of andragogy. It uses an i ndividual approach and takes into account the internal motivation processes of the learners. Educators who teach adults functional literacy are subject to strict requirements that are defined by the collection of rules and requirements of the "Profile of the teacher of literacy".

Резюме. Что касается работы со взрослым населением Франции, то нами выделены особенности новой формы организации непрерывного профессионального образования взрослых в этой стране – образовательной структуры ГРЕТА. Национальная образовательная структура ГРЕТА в наше время представляет собой основную организацию, занимающуюся непрерывной профессиональным образованием взрослых во Франции. В состав Бельгии входят 3 языковые сообщества – фламаномовна, франкоязычная и немецкоязычная. На фоне федеративного устройства, языкового расслоения населения существуют проблемы. В стране ведется борьба с неграмотностью взрослого населения, в результате чего повышается общий уровень образования.
Organization of adult education in France and Belgium
https://periodicals.karazin.ua/pedagogy/article/view/12506/11905
Keywords: освіта дорослих; Франція; Бельгія; освітня структура ГРЕТА; мовні спільноти; adult education; France; Belgium; GRETA educational structure; language communities